Republic of Palau : Staff Report for the 2003 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
The Republic of Palau is a small island economy, heavily dependent on tourism and external assistance. Economic growth has been modest in the last few years and inflation is low. The authorities launched a wide range of reform initiatives since 2001, but several important ones have stalled in the legislative process. Although the banking regulatory framework still needs improvements for effective implementation, a tax reform package, a new foreign investment law, a statistics law, and proposals related to streamlining the executive and legislative branch have not yet been enacted.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet